2002
DOI: 10.1046/j.1365-2621.2002.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, physicochemical and organoleptic changes in dry‐salted olives of Thassos variety stored under different modified atmospheres at 4 and 20 °C

Abstract: Microbiological, physico-chemical and organoleptic changes were studied in dry-salted olives, cv. Thassos, stored under different atmospheres (100% carbon dioxide and nitrogen, 40% CO 2 /30%O 2 /30%N 2 and air) at 4 and 20°C for 180 days. The initial microbial flora comprised of yeasts, no lactic acid bacteria, enterobacteria, pseudomonads or Staphylococcus aureus were detected, as the low water activity/high salt content does not favour their growth. At 4°C, the population of yeasts declined steadily througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 7 publications
2
42
0
Order By: Relevance
“…This level is fairly common in home-made or in dry-salted table olives (Panagou et al, 2002) but not in Manzanilla-Aloreña in which the production of titratable acidity is normal (Garrido Fernández et al, 2002). The fermentation (by yeasts) process of cracked olives was always more rapid than any of the other untreated (natural) fruits, a circumstance that may accelerate the degradation of chlorophylls and the browning of the olive surface and brine (Garrido Fernández et al, 2002).…”
Section: Physicochemical and Microbiological Evolution During Storagementioning
confidence: 99%
See 2 more Smart Citations
“…This level is fairly common in home-made or in dry-salted table olives (Panagou et al, 2002) but not in Manzanilla-Aloreña in which the production of titratable acidity is normal (Garrido Fernández et al, 2002). The fermentation (by yeasts) process of cracked olives was always more rapid than any of the other untreated (natural) fruits, a circumstance that may accelerate the degradation of chlorophylls and the browning of the olive surface and brine (Garrido Fernández et al, 2002).…”
Section: Physicochemical and Microbiological Evolution During Storagementioning
confidence: 99%
“…The tendency of the olive fruits to loose freshness with storage time may be not only due to the progressive polymerization of phenols but also to the degradation of chlorophylls and the subsequent decrease in the green surface colour (Mínguez-Mosquera et al, 1994). Panagou et al (2002) showed an initial decline in yeast population followed by a steady increase until the end of the storage period of dry-salted olives. In directly brined olives, an initial microbial inactivation was related to a lack of nutrients because of their slow solubilisation from whole fruits (García et al, 1992).…”
Section: Physicochemical and Microbiological Evolution During Storagementioning
confidence: 99%
See 1 more Smart Citation
“…2008). This method is similar to the methodology applied in other countries (Panagou et al. 2002; Panagou 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since dry‐salted olives are not packaged in brine, an alternative would be to use modified atmospheres, such as CO 2 , that could irreversibly impact the survival of fungi (Panagou 2006). Packaging of olives under modified atmospheres effectively controls the growth of fungi, thus minimizing the potential production of mycotoxins (Panagou et al. 2002).…”
Section: Introductionmentioning
confidence: 99%